1994
DOI: 10.2105/ajph.84.4.657
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent occupational injuries requiring hospital emergency department treatment: a nationally representative sample.

Abstract: Data from a nationally representative sample of emergency departments for the 6-month period July through December 1992 were used to examine nonfatal occupational injuries sustained by adolescents aged 14 through 17 years. There were 679 occupational injuries, corresponding to an estimated 37,405 injuries nationwide. Males constituted 65.8% of the injury victims. The injury rate for males was 7.0 per 100 full-time employees, compared with 4.4 for females. Lacerations to the hand or finger accounted for 25.6% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 12 publications
10
74
1
2
Order By: Relevance
“…Extrapolating from data collected as part of the Consumer Product Safety Commission's National Electronic Injury Surveillance System, Layne et al (44) estimated that 64,100 injuries among teenager workers who were <18 years of age were treated in emergency departments in 1992, a number that was down from a prior estimate of 75,000 during 1982 (25). The analysis by Layne et al (44) showed that both the highest proportion (54%) and highest injury rates (6.3/100 full-time employees) occurred among workers in retail trades.…”
Section: Emergency Room Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolating from data collected as part of the Consumer Product Safety Commission's National Electronic Injury Surveillance System, Layne et al (44) estimated that 64,100 injuries among teenager workers who were <18 years of age were treated in emergency departments in 1992, a number that was down from a prior estimate of 75,000 during 1982 (25). The analysis by Layne et al (44) showed that both the highest proportion (54%) and highest injury rates (6.3/100 full-time employees) occurred among workers in retail trades.…”
Section: Emergency Room Recordsmentioning
confidence: 99%
“…The analysis by Layne et al (44) showed that both the highest proportion (54%) and highest injury rates (6.3/100 full-time employees) occurred among workers in retail trades. For males working in retail trades, the proportion was 66%, with injury rates of 7.0/100 for full-time male employees vs 4.4/100 among full-time female employees).…”
Section: Emergency Room Recordsmentioning
confidence: 99%
“…Restaurant work among young workers has also been noted as hazardous in a number of U.S. studies. 10,11 In the study, boys had more severe work injuries than girls. Girls' injuries were mainly associated with domestic work, while those from boys were associated with rural activities, cattle or brick making.…”
Section: Discussionmentioning
confidence: 83%
“…Further, back pain in particular is of concern in adolescence, and may place these young workers at greater risk for future musculoskeletal problems. Risks of severe and even fatal injuries occur most frequently among boys rather than girls, 2,3,5,6,10,18 indicating different types of employment activities and possibly job demands. 6,18 In this study, data regarding fatal injuries were not collected.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] The nature of hand injuries caused by occupational accidents differs with respect to the developmental level of the country and regional differences in the type of industry within the same country. In a large retrospective analysis involving 37,405 nonfatal occupational accidents, Layne et al [15] investigated occupational injuries in the United States within a six-month period during 1992, and found that finger and hand injuries were the most common, with a rate of 44.3%. The authors reported that the most common injury types were lacerations and burns, with rates of 39.0% and 17.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%